PATERNAL AND MATERNAL REFLECTIVE FUNCTIONING IN THE WESTERN AUSTRALIAN PEEL CHILD HEALTH STUDY. Issue 5 (21st August 2017) - Cooke, Dawson; Priddis, Lynn; Luyten, Patrick; Kendall, Garth; Cavanagh, Robert
ABSTRACT: While past research on the care of infants has been mostly with mothers, in recent times there has been a renewed attention to the father–infant relationship. This study examined differences between mother and father parental reflective functioning (PRF) or parental mentalizing; that is, the parental capacity to reason about their own and their children's behaviors by taking into consideration intentional mental states. Data were collected from 120 couples with a 1‐year‐old child who were participants in the West Australian Peel Child Health Study. Parental mentalizing was assessed using the Parental Reflective Functioning Questionnaire (PRFQ; Luyten, Mayes, Nijssens, & Fonagy, 2017 ). Results showed that mother and father mentalizing with their children was independent and that mothers scored slightly higher levels of mentalizing than did fathers. Paternal mentalizing was weakly associated with family income and father education, and was more strongly associated with family functioning than with maternal mentalizing. Implications for theorizing on PRF and fatherhood more generally are discussed.